Interactive Communication Strategies in Online Learning: A Case Study - Hairun Nissa; Irfan Dedi (Dinasti Publisher, 2025)
This study aims to map and analyze positive interactional communication strategies between teachers and students in online learning, focusing on SD Islam Anak Saleh, Malang, during the first semester of the 2021/2022 academic year. The research highlights how teachers implement communication strategies to create a comfortable and conducive online learning environment. Using a qualitative case study approach, data were collected through non-participant observations, in-depth interviews, and document analysis. The findings reveal that teachers establish positive communication strategies through four key elements: care, clarity, credibility, and celebration. These strategies support a more effective and structured learning experience. Furthermore, the traditionally asymmetrical power relations between teachers and students have shifted toward a more flexible and participatory model, emphasizing dynamic multi-party collaboration between teachers, students, and parents. The study contributes theoretically by simplifying Gao’s communication strategies into operational methods, and enriching the understanding of flexible and participatory power relations involving multi-party collaboration in online learning. Practically, these findings provide educators and policymakers with a framework for developing more inclusive, adaptive, and collaborative interactional communication strategies, suited for the digital education era.